Discussion platform “Religious studies in Modern Kazakhstan: Intergration of the Science and Education” in the framework of the VI International Farabi Forum, April 2d,2019 (Eurasian Journal of Religious Studies, 2019)
In the framework of VI International Farabi Forum the Discussion Platform "Religious studies in the Modern Kazakhstan: Integration of the Science and Education" (April 2 2019) was held.